METHODOLOGY FOR DEVELOPING THE PROFESSIONAL COMPETENCE OF PROSPECTIVE PRIMARY SCHOOL TEACHERS BASED ON PEDAGOGICAL COACHING AND ARTIFICIAL INTELLIGENCE - Akramova Zukhra Botir qizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract. This article theoretically and methodologically substantiates a methodology for developing the professional competence of prospective primary school teachers through the integration of pedagogical coaching and artificial intelligence (AI) tools. The methodology combines the competency-based approach, reflective practice, collaborative learning, microteaching, criterion-referenced assessment (rubric/checklist), and multi-source feedback (self/peer/mentor) into a single cyclical framework. AI tools support the methodological process as a “coach assistant” by preparing a bank of powerful questions for GROW sessions, structuring reflective journals, identifying rubric indicators on the basis of evidence, and generating alternative individualized improvement plans. The article proposes stages for an 8–12-week module, monitoring indicators, a lesson analysis rubric, and a sample peer-feedback protocol. Ethical safety principles such as privacy, fairness, human-in-the-loop, and academic integrity are presented as essential methodological conditions. As a result, an integrated methodological solution has been developed to support the step-by-step development of the prospective teacher’s methodological-didactic, assessment, communicative, and reflective competences on the basis of evidence.